Resistance Evaluation for Native Potato Accessions against Late Blight Disease and Potato Cyst Nematodes by Molecular Markers and Phenotypic Screening in India - Dalamu; Jagesh Kumar Tiwari; Aarti Bairwa; Nisha Bhatia; Rasna Zinta; Nimisha Kaushal; Vinod Kumar; Ashwani K. Sharma; Sanjeev Sharma; Babita Choudhary; Satish Kumar Luthra; Tanuja Buckseth; et al. (Life, 2022)
The potato originated in southern Peru and north-western Bolivia (South America). However, native accessions have also been cultivated in India for many years. Late blight, caused by the fungus Phytophthora infestans, is the most devastating potato disease, while potato cyst nematode (Globodera spp.) (PCN) is another economically significant quarantine-requiring pest in India. In this study, we have generated a new Indian native collection of 94 potato accessions collected from different parts India. These accessions were screened against late blight and potato cyst nematode resistance by using gene-based molecular markers and phenotypic screening methods. Marker assisted selection using R1 gene-specific marker CosA210 revealed a late blight resistance gene in 11 accessions. PCN resistance bands were found in 3 accessions with marker TG689141, 5 accessions with marker 57R452, and 1 accession having Gro1-4-1602 marker for G. rostochiensis (Ro1,4), while 64 accessions amplified marker HC276 indicating G. pallida (Pa2,3) resistance gene (GpaVvrn QTL). On the other hand, phenotypic screening against late blight resistance under natural epiphytic conditions (hot-spot) revealed three accessions with high resistance, while others were resistant (1 accession), moderately resistant (5 accessions), susceptible (29 accessions), and highly susceptible (56 accessions). For G. rostochiensis (golden cyst nematode) and G. pallida (white cyst nematode) resistance, accessions were grouped into highly resistant (3, 3), resistant (0, 2), moderately resistant (6, 29), susceptible (32, 30), and highly susceptible (53, 30), respectively, for the two PCN species. Collectively, we identified promising accessions with high resistance to late blight (JG-1, Kanpuria Safed, and Rangpuria), and also highly resistant to both Globodera species (Garlentic, Jeevan Jyoti, and JG-1). Our findings suggested that these accessions would be useful for late blight and PCN resistance breeding, as well as future molecular studies in potatoes.